Solar activities associated with 3He-rich solar energetic particle events observed by Solar Orbiter - Nitta, Nariaki V.; Bučík, Radoslav; Mason, Glenn M.; Ho, George C.; Cohen, Christina M. S.; Gómez-Herrero, Raúl; Wang, Linghua; Balmaceda, Laura A. (Frontiers in Astronomy and Space Sciences, 2023)
A series of 3He-rich solar energetic particle (SEP) events was observed by Solar Orbiter in May 2021 at a radial distance of 0.95~AU. An isolated active region AR 12824 was likely the ultimate source of these SEP events. The period of the enhanced flux of 3He was also a period of frequent type III bursts in the decametric-hectometric range, confirming their close relationship. As in past studies, we try to find the solar activities possibly responsible for 3He-rich SEP events, using the type III bursts close to the particle injection times estimated from the velocity dispersion. But this exercise is not as straightforward as in many of the past studies since the region produced many more type III bursts and jet-like eruptions than the SEP injections. We may generalize the solar activities for the 3He-rich SEP events in question as coronal jets, but their appearances do not necessarily conform to classic jets that consist of a footpoint and a spire. Conversely, such jets often did not accompany type III bursts. The areas that produced jet-like eruptions changed within the active region from the first to the second set of 3He-rich SEP events, which may be related to the extended coronal mass ejection that launched stealthily.